Accrediting Indigenous Australian Content and Cultural Competency Within the Bachelor of Laws - Annette Gainsford; Marcus Smith; Alison Gerard (Legal Education Review)
The most recent version of the Council of Australian Law Deans Law School Standards calls for embedding Indigenous cultural competence in Australian law degrees as a matter of best practice. To support this work Universities Australia has produced several reports that establish a best practice framework for Indigenous cultural competence, which is reinforced by the Universities Australia Indigenous Strategy 2017-2020. Universities and law schools have a responsibility to drive this change, to be reflective, and to contribute to an expanding community of practice on Indigenous cultural competence in legal education. This paper explores how Charles Sturt University embedded Indigenous cultural competency across core curriculum content of the Bachelor of Laws. The authors provide a detailed explanation of the course pedagogical mapping and specific subject content that was submitted for institutional accreditation.